2023
DOI: 10.1186/s12875-023-02097-3
|View full text |Cite
|
Sign up to set email alerts
|

The effects of an innovative GP-physiotherapist partnership in improving COPD management in primary care

Abstract: Background Evidence suggests that management of people with Chronic Obstructive Pulmonary Disease (COPD) in primary care has been suboptimal, in particular, with low referral rates to pulmonary rehabilitation (PR). The aim of this study was to evaluate the effectiveness of a GP-physiotherapist partnership in optimising management of COPD in primary care. Methods A pragmatic, pilot, before and after study was conducted in four general practices in A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 44 publications
0
0
0
Order By: Relevance
“…Only two (4%) studies reported on eating behaviour and both found improvements, described as a decrease in total energy intake and increase in protein intake [86] and an increase in eating a balanced diet [76] (Figure 3A). Nine (19%) studies reported on PA levels, of which five found an increase in PA level [64,67,70,76,96] and four found no effect [63,65,69,95]. Out of 10 (21%) studies reporting an outcome on smoking cessation, only one found a decrease in the number of current smokers [66], while the other nine studies did not find any effect [35,59,63,70,71,76,89,90,95].…”
Section: Reported Outcomes and Possible Effects Of Clis Behavioural O...mentioning
confidence: 97%
See 4 more Smart Citations
“…Only two (4%) studies reported on eating behaviour and both found improvements, described as a decrease in total energy intake and increase in protein intake [86] and an increase in eating a balanced diet [76] (Figure 3A). Nine (19%) studies reported on PA levels, of which five found an increase in PA level [64,67,70,76,96] and four found no effect [63,65,69,95]. Out of 10 (21%) studies reporting an outcome on smoking cessation, only one found a decrease in the number of current smokers [66], while the other nine studies did not find any effect [35,59,63,70,71,76,89,90,95].…”
Section: Reported Outcomes and Possible Effects Of Clis Behavioural O...mentioning
confidence: 97%
“…Nine (19%) studies reported on PA levels, of which five found an increase in PA level [64,67,70,76,96] and four found no effect [63,65,69,95]. Out of 10 (21%) studies reporting an outcome on smoking cessation, only one found a decrease in the number of current smokers [66], while the other nine studies did not find any effect [35,59,63,70,71,76,89,90,95]. No studies measured the effects on alcohol consumption or sleeping behaviour and only one study reported a decrease in stress level [94].…”
Section: Reported Outcomes and Possible Effects Of Clis Behavioural O...mentioning
confidence: 99%
See 3 more Smart Citations